Model Integratif Industrialisasi Modern dalam Pengembangan Industri Daerah: Sinergi Teknologi, Sumber Daya Manusia, Kebijakan, dan Pasar - Muhammad Faiz Aulia Zuhud; Rafli Maulana Damarasyah; Muhamad Yasin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Modern industrialization is one of the primary strategies for driving economic growth and regional industrial development amidst the dynamics of globalization and digital transformation. The success of industrialization is determined not only by technological adoption but is also influenced by the quality of human resources, government policy support, and the ability to access markets effectively. This study aims to analyze an integrative model of modern industrialization that combines four main components—technology, human resources, policy, and markets—in supporting regional industrial development. The research method used is a literature review (library research) with a descriptive-analytical approach. Data were obtained from scientific journals, academic books, and official reports relevant to industrialization, economic development, and industrial management. The findings indicate that the success of modern industrialization requires the simultaneous integration of technological innovation, human resource capacity building, adaptive policies, and market access expansion. The integration of these four components is capable of enhancing productivity, industrial competitiveness, job creation, and sustainable regional economic growth. Therefore, local governments need to develop industrial policies integrated with digital transformation, workforce competence strengthening, and the development of a competitive market ecosystem to support modern industrialization.